2011
DOI: 10.1177/1062860611404049
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Clinical Pathway to Improve Colorectal Cancer Outcomes

Abstract: The aims of this preintervention and postintervention study were to monitor and evaluate the clinical pathway (CP) for colorectal cancer (CRC) over a 5-year period and to compare 2 groups of patients (before and after the intervention) with regard to different variables of effectiveness. Group I comprised 68 patients who underwent planned surgery between January 2002 and January 2003. Group II comprised a sample of 202 patients who underwent surgery between January 2004 and December 2008. No significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Patient/caregiver engagement by way of involving patients in generating the integrated care plan and accounting for patient (and/or caregiver preferences) featured prominently in plans focused on survivorship and palliative stages [ 43 59 62 63 78 ]. Some studies also reported allowing patients to access the integrated care plan through an electronic or paper format to enable patients to be actively engaged in treatment planning and delivery during their cancer journey [ 35 59 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient/caregiver engagement by way of involving patients in generating the integrated care plan and accounting for patient (and/or caregiver preferences) featured prominently in plans focused on survivorship and palliative stages [ 43 59 62 63 78 ]. Some studies also reported allowing patients to access the integrated care plan through an electronic or paper format to enable patients to be actively engaged in treatment planning and delivery during their cancer journey [ 35 59 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Provider-level outcomes included provider satisfaction with the use of integrated care plans, i.e., workflow interruptions, ease of use, time associated with generating or discussing the integrated care plan with patients [ 74 83 ], and provider’s perceptions of benefits (i.e., improvements in information sharing between providers) [ 71 74 79 80 83 98 ]. System-level indicators included common healthcare utilization measures such as length of stay, complication rates (post-operative), hospital readmissions, and cost (hospital-related costs and the cost of delivering the integrated care plan) [ 36 39 40 41 43 46 47 48 49 51 54 55 56 57 58 60 61 67 85 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical pathway for colorectal carcinoma, this tool was developed by the researcher after extensive review of related literatures (Aledo, 2011) this tool was applied on the study group. It was used to measure the reliability of the developed tools.…”
Section: Development Of Colorectal Surgery Clinical Pathwaymentioning
confidence: 99%